2022
DOI: 10.1039/d2py00067a
|View full text |Cite
|
Sign up to set email alerts
|

Straightforward synthesis of multifunctional porous polymer nanomaterials for CO2 capture and removal of contaminants

Abstract: Wastewater and increasing atmospheric CO2 level are two major environmental challenges that pose a threat to human life. We report a straightforward preparation of functional mesoporous polymer nanomaterials with bearing...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…These results confirm that the presence of hierarchical pores within activated SIS-derived carbons can lead to excellent CO 2 capture performance, which is comparable to or higher than several recent reports. 72,73 For example, a very recent work from Mohamed et al reported the development of porous organic polymers linked with crown ether and benzoxazine through a multi-step procedure, which can uptake CO 2 up to 5.8 mmol g À1 at 0 1C. 74 Moreover, using the CO 2 sorption capacity of activated SISderived carbons at 0 1C and 25 1C and various pressure, the heat of adsorption for these samples can be determined according to Clausius-Clapeyron equation, which is in the range of 15-28 kJ mol À1 , consistent with physisorption mechanism and suggesting a small amount of energy would be enough for sorbent regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…These results confirm that the presence of hierarchical pores within activated SIS-derived carbons can lead to excellent CO 2 capture performance, which is comparable to or higher than several recent reports. 72,73 For example, a very recent work from Mohamed et al reported the development of porous organic polymers linked with crown ether and benzoxazine through a multi-step procedure, which can uptake CO 2 up to 5.8 mmol g À1 at 0 1C. 74 Moreover, using the CO 2 sorption capacity of activated SISderived carbons at 0 1C and 25 1C and various pressure, the heat of adsorption for these samples can be determined according to Clausius-Clapeyron equation, which is in the range of 15-28 kJ mol À1 , consistent with physisorption mechanism and suggesting a small amount of energy would be enough for sorbent regeneration.…”
Section: Resultsmentioning
confidence: 99%